Generating a national snapshot of all publicly reported investments in ecosystem and species conservation across public, private, and philanthropic finance - Alice Stuart; Sophus O. S. E. zu Ermgassen (Ambio, 2026)
Abstract Scaling up investment in ecosystems is a national and international public policy priority. Evaluations of the total amount spent have been severely criticised, with a lack of transparent reporting, especially of private finance flows, a known limitation. We provide a country-wide snapshot of investment in nature in the UK based on publicly available data, estimating total annual nature finance flows in the UK of ~£1.15bn. Public investment in agri-environment (£389.1m) and grant schemes (£314.8m) accounted for over 60% of identified flows. Private financial flows (£142.4m) consisted of corporate philanthropy (£71.5m), return-seeking investment and loans (£50.7m), and credit and unit purchases (£20.2m). Estimated flows from NGOs and philanthropic grants totalled £388.5m. Interactions between flows mean double counting must be considered when summing. We find major public transparency gaps in nature finance flows, undermining efforts to understand the both the extent of nature finance flows and their effectiveness for nature recovery.